Implications of intermediaries in global logistics of foreign trade - C, Muthuvelayutham; R, Karuppasamy (Journal of Management and Science, 2012)
The world towards traveling in integrated phenomena which require more needs. That it is fulfilling by the trade between the countries. Because of each country continuously transferthe goodsto other country as same as another country transferring to that country. That make as a global logistics belongs to foreign trade. Also it clears from the past literatures. Being a shipper or buyer can export or import the goods as directly they meet more complexity like business contacts, forwarding, transportation arrangements and customs clearanceetc.By those reasons, a shipper and buyer can export and import using indirect involvementmeans that the firm participates in worldwidecommerce through an intercessor and does not deal with foreign customers or markets. In that situation, the intermediaries get the huge place of contribution in global logistics belongs to foreign trade.